Understanding How Marketing Strategies Inform Consumer Purchasing Decisions: A Qualitative Inquiry at PT Poin Medika, Yogyakarta, Indonesia - Sentosa, Agung Mulya; Purwoko, Purwoko; Setiawan, Zunan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This qualitative inquiry explores how marketing strategies shape consumer purchasing decisions at PT Poin Medika in Yogyakarta, Indonesia. The study is grounded in the view that purchasing behavior is not merely a reaction to promotional cues, but a negotiated process influenced by perceptions, trust, and experiential signals embedded in everyday consumer brand interactions. As patient-oriented service industries grow increasingly competitive, understanding these subtler decision drivers becomes essential for crafting strategies that resonate authentically with local consumers. Using a qualitative descriptive design, data were gathered through semi-structured interviews with customers and key marketing personnel, complemented by on-site observations. All transcripts and field notes were coded and analyzed using NVivo to identify recurring patterns and relational themes. The NVivo analysis revealed three dominant clusters trust-anchored communication, where transparent information and empathetic tone strengthened perceived reliability; service experience cues, including staff attentiveness and perceived service efficiency, which shaped emotional comfort and purchase readiness; and value interpretation, reflecting how consumers evaluated the alignment between pricing, service quality, and personal health needs. The synthesis of these themes indicates that effective marketing at PT Poin Medika is less about persuasive tactics and more about cultivating relational assurance and meaningful service encounters. The findings suggest that marketing strategies rooted in clarity, human warmth, and consistent service delivery foster stronger purchase intentions. This study underscores the strategic importance of experiential and trust-based communication in guiding consumer decision-making within healthcare-related service contexts.